2007
DOI: 10.1111/j.1471-0528.2007.01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Leisure time physical exercise during pregnancy and the risk of miscarriage: a study within the Danish National Birth Cohort

Abstract: Objective To examine the association between leisure time physical exercise during pregnancy and the risk of miscarriage.Design Prospective study with elements of retrospective data collection. Setting Denmark 1996-2002.Population A total of 92 671 pregnant women enrolled in the Danish National Birth Cohort and interviewed subsequently.Methods Data on exercise during pregnancy and potential confounders were obtained through computer-assisted telephone interviews either during pregnancy or after an early miscar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“…The participants in the DNBC reported leisure time physical exercise and these data were used to assess the risk of miscarriage according to such activity. Against the authors' expectations a strong and stepwise increasing relation was found between amount of exercise and risk of miscarriage [17]. In contrast, studies of physical activity and the risk of preterm birth and fetal growth restriction showed a reduced risk of preterm birth among the almost 40% of women who engaged in some kind of exercise during pregnancy in comparison with nonexercisers and no sizeable effects on fetal growth measures [18,19].…”
Section: Obesity and Physical Exercise During Pregnancymentioning
confidence: 81%
“…The participants in the DNBC reported leisure time physical exercise and these data were used to assess the risk of miscarriage according to such activity. Against the authors' expectations a strong and stepwise increasing relation was found between amount of exercise and risk of miscarriage [17]. In contrast, studies of physical activity and the risk of preterm birth and fetal growth restriction showed a reduced risk of preterm birth among the almost 40% of women who engaged in some kind of exercise during pregnancy in comparison with nonexercisers and no sizeable effects on fetal growth measures [18,19].…”
Section: Obesity and Physical Exercise During Pregnancymentioning
confidence: 81%
“…Common risk factors include increased maternal age, high pre-pregnancy body mass index (BMI) and low serum progesterone levels. (11)(12)(13)(14) More recently, lifestyle factors such as caffeine intake, (15) exercise, (16) stress, (9,17) exposure to cigarette smoke, (18,19) and alcohol consumption (12,20,21) have also been implicated as risk factors. Some studies have documented the proportion of women who had experienced a threatened miscarriage who subsequently go on to experience a complete miscarriage.…”
Section: Introductionmentioning
confidence: 99%
“…During the first trimester of pregnancy, the ideal exercise time ranged from 45 to 74 min per week; as a retrospective study though recall bias may have influenced these values. In the second and third trimesters there were no associations with miscarriages and amount of exercise (Madsen et al 2007). Additionally, one study suggests too much exercise ([5 times per week), similar to not enough (B2 times per week), may be associated with an increased likelihood of delivering a small for gestational age baby (Campbell and Mottola 2001).…”
Section: Frequency and Durationmentioning
confidence: 93%
“…Aerobic exercises which are non-impact and nonweight bearing, such as swimming and stationary cycling are the safest during all trimesters of pregnancy. Research has demonstrated that swimming is the safest aerobic activity throughout pregnancy, due to the low impact nature and improved thermoregulation (Madsen et al 2007). However, swimming and stationary cycling require a gym membership or costly equipment which is not feasible for many pregnant women.…”
Section: Type Of Aerobicmentioning
confidence: 98%
See 1 more Smart Citation